An mHealth intervention programme to promote healthy behaviours and prevent adolescent obesity (TeenPower): A study protocol. (10th January 2019) - Sousa, Pedro; Duarte, Emília; Ferreira, Regina; Esperança, Ana; Frontini, Roberta; Santos‐Rocha, Rita; Luís, Luís; Dias, Sara S.; Marques, Nuno
Abstract: Aim: This paper describes the design and rationale of multicenter practice‐based research that aims to develop and evaluate an innovative mobile health (mHealth) intervention programme directed to promote healthy behaviours and prevent adolescent obesity. Design: This study is designed as a non‐randomized controlled trial with a three‐arm structure. Methods: Twelve to 16 years old participants will be recruited from schools, with access to the Internet and smartphone/tablet devices. The intervention group will be invited to engage in the TeenPower mHealth programme and divided into two subgroups: Group A (additionally engaged in a structured school‐based intervention programme) and Group B (only engaged in the mHealth programme). The mHealth app includes educational resources, self‐monitoring, social support, interactive training modules and motivational tools. The control group will only follow the structured school‐based intervention programme. The intervention length will be 3 months, including the direct support of an interdisciplinary team (nursing, nutrition, sports, psychology, among others). This research was approved and funded in August 2017. Discussion: The positive evaluation of the intervention programme will stimulate the inclusion of technologies in the promotion of salutogenic behaviours and obesity prevention. Impact: Adolescent obesity reached epidemic proportions. It is urgent to find effective prevention strategies to induce change at the individual, family and community level. If effective, this protocol can be used by health and exercise professionals in improving community interventions tailored to teenagers. Abstract : 目的: 本文描述了基于多中心实践的研究的设计和原理, 旨在开发和评估促进健康行为和预防青少年肥胖的创新性移动医疗(mHealth)干预方案。 设计: 本研究设计为具有三臂结构的非随机对照试验。 方法: 通过网络和智能手机/平板设备等, 从学校招募12至16岁的参与者。邀请干预组参与TeenPower移动医疗方案, 并分成两个小组:A组(另外参与结构化的校本干预方案)和B组(仅参与移动医疗方案)。移动医疗手机软件包括教育资源、自我监控、社会支持、交互式培训模块和激励工具。对照组只遵循在学校进行的结构化干预方案。干预时间为3个月, 包含跨学科团队的直接支持(护理、营养、体育、心理学等)。该研究于2017年8月获得批准和资助。 讨论: 对干预方案的积极评价将有利于在促进有益健康的举措和肥胖预防工作中纳入该技术。 影响: 青少年肥胖已成为一种流行病。找到能在个人、家庭和社区层面引发变革的有效预防战略是当务之急。如果有效, 该方案可由健康和运动专业人员用于改善针对青少年的社区干预措施。